Remote collaboration in immersive mixed reality - Latif, Freeman (2015)
The recent availability of commodity VR hardware enables inexpensive creation of immersive games and applications that induces a strong sense of personal presence. This dissertation explores whether the same can be said about the sense of co-presence, and how remote collaboration can be facilitated in an immersive mixed reality environment where users can see each other and manipulate virtual objects. The remote user is represented as a 3D coloured mesh, resembling the real person. The design and implementation of such an environment is discussed, and a user study was conducted which compares 3 different remote user representation modes: skeletal, plain mesh and coloured mesh. The user study shows that the availability of colour and depth cues is vital in facilitating the feeling of co-presence.